2004
DOI: 10.1300/j175v04n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis as a Substitute for Alcohol: A Harm-Reduction Approach

Abstract: ABSTRACT. Ninety-two Northern Californians who use cannabis as an alternative to alcohol obtained letters of approval from the author. Their records were reviewed to determine characteristics of the cohort and efficacy of the treatment, which was defined as reduced harm to the patient. All patients reported benefit, indicating that for at least a subset of alcoholics, cannabis use is associated with reduced drinking. The cost of alcoholism to individual patients and society at large warrants testing of the can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 5 publications
1
30
1
Order By: Relevance
“…Mikuriya found in 2001 and 2004 that 55% and 53% of patients respectively reported having one or two alcoholic parents [12,13]. One quarter of this sample reported growing up in an alcoholic or abusive household.…”
Section: Discussionmentioning
confidence: 95%
“…Mikuriya found in 2001 and 2004 that 55% and 53% of patients respectively reported having one or two alcoholic parents [12,13]. One quarter of this sample reported growing up in an alcoholic or abusive household.…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with previous findings (Compton et al, 2017), medical use only was negatively associated with drug or alcohol use disorders and unmet need for drug use disorder treatment among both males and females. This is probably due to use of medical marijuana as a substitute for alcohol or other drugs (Lucas et al, 2016; Reiman, 2007; Reiman, 2009), which might be related to reduction in alcohol use and alcohol-related problems (Mikuriya, 2004). Medical use only was also negatively associated with opioid use disorder among females.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some evidence that cannabis use impacts alcohol use severity adversely, there are a number of contradictory findings from case report and correlational studies suggesting that cannabis can substitute for alcohol and reduce drinking . High rates of cannabis substitution for alcohol have been reported by medical cannabis patients and their doctors , although results are limited by retrospective self‐report and selection bias. A 30‐year prospective study of alcohol abusers showed that almost half maintained a year of alcohol abstinence, with some claiming to substitute cannabis for alcohol .…”
Section: Introductionmentioning
confidence: 99%
“…A 30‐year prospective study of alcohol abusers showed that almost half maintained a year of alcohol abstinence, with some claiming to substitute cannabis for alcohol . Some even propose that medical cannabis could help individuals with AUD reduce drinking ; however, these recommendations are based upon retrospective data, highlighting the need for more rigorous research in this area.…”
Section: Introductionmentioning
confidence: 99%